Waste sorting education for preschool children in Silaberanti Village, Palembang City - Rahmi Garmini; Abelia Abelia; Abel Finalya Amanda; Adelia Elvetha; Adelia Intan Kencana; Ade Karunia; Ade Melani; Alfandi Alfandi; Amelia Prahastuti; Anugrah Pratama; Della Rizki Oktrariana (Universitas Muhammadiyah Magelang, 2024)
Waste poses a ubiquitous challenge across Indonesia, negatively impacting terrestrial, aerial, and marine environments. This community service initiative aimed to enhance the knowledge of preschool children regarding waste sorting practices. The implementation method involved educational sessions and the distribution of leaflets. Prior to the educational sessions, a pre-test was administered to assess the children's existing knowledge. Subsequently, an intervention was conducted, providing health education on waste sorting. Following the intervention, a post-test was administered to evaluate the improvement in the children's knowledge. The results indicated a significant increase in knowledge before and after the educational sessions, with an average pre-test score of 6 and an average post-test score of 8. This initiative effectively enhanced the knowledge of preschool children at PAUD Silaberanti regarding the sorting of both organic and inorganic waste.